Analisis Psikologi Tokoh dan Nilai Moral dalam Novel Surat Dari Bapak Karya Gol A Gong serta Pemanfaatannya sebagai Bahan Ajar di SMA - Saraswati, Saraswati; Al Gadri, Henri Henriyan; Fauzan, M. Irfan (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2023)
This study aims to (1) describe the psychological aspects of the main character in Gol A Gong's Novel Surat dari Bapak; (2) describe the moral values ​​in the novel Surat Dari Bapak by Gol A Gong; and (3) describe its use as teaching materials in SMA. The main character psychological theory used in this study is the psychoanalytic theory by Sigmund Freud which consists of three personality structures, namely: the id found 9 data, the ego found 4 data, and the superego found 3 data. Furthermore, the theory of moral values ​​used is the fictional assessment theory put forward by Nurgiyantoro which consists of three relations of problems in life, including the relationship between humans and oneself found 11 data which include firm stance, calm, careful, self-esteem, independent, and aware error; human relations with the social sphere found 14 data including loyalty, social care, courtesy, parental love for children, and critical; and the relationship between humans and God found 3 data including believing in the existence of God. This type of research is descriptive qualitative. The research subject is the novel Surat dari Bapak by Gol A Gong. The object of research is the psychology of the main character and the moral value of the novel Surat dari Bapak. The source of the data is the story description of the novel Surat dari Bapak by Gol A Gong published by Puspa Swara. This data collection technique uses observation techniques. The research instrument was a researcher assisted by a literary support book and notes. The data analysis technique uses content analysis techniques.